Exploring the Role of Professional Accounting Ethics in Safeguarding Financial Reporting Integrity in the Digitalization Era - Silaban, Barnabas Tridig; Aziz, Abdul; Fauziya, Ahada Nur; Febe, Jesslyn (Universitas Syiah Kuala, 2025)
This study explores the role of professional accounting ethics in safeguarding the integrity of financial reporting in the digitalization era. The research adopts a qualitative library-based methodology to analyze scholarly literature, regulatory documents, and prior research related to ethical conduct in digital accounting environments. Findings reveal that digitalization has introduced both opportunities and ethical challenges for financial reporting, including automation risks, cybersecurity threats, and increased potential for data manipulation. While traditional ethical frameworks remain relevant, they are insufficient to address digital-specific dilemmas, highlighting the need to integrate digital ethics, technological literacy, and ethical resilience into professional standards. Results further indicate that ethical awareness, competency development, organizational culture, and updated ethical codes are essential for ensuring transparency, accountability, and credibility of financial information in a technologically advanced environment. This study contributes to academic discourse by emphasizing the urgency of strengthening ethical foundations in conjunction with technological advancements to maintain public trust in financial reporting. Strategic implications suggest that ethical digitalization not only preserves reporting integrity but also enhances stakeholder confidence and sustainable organizational performance.